Geometry optimization of a novel M-like flow field in a proton exchange membrane fuel cell. (15th January 2021) - Yang, Chen; Wan, Zhongmin; Chen, Xi; Kong, Xiangzhong; Zhang, Jing; Huang, Taiming; Wang, Xiaodong
Highlights: Two geometrical parameters of the M−like channel in a PEMFC were investigated. The M−like channel has more uniform and large concentration distribution of oxygen. EEC was utilized to evaluate the comprehensive performance of a PEMFC. Performance of the optimum M−like channel is 16% higher than the parallel channel. The M−like channel has better comprehensive performance that the parallel channel. Abstract: In order to optimize the geometry of the M−like flow field, numerical simulations were performed by virtue of the fuel cell module in ANSYS® FLUENT® software package. Two geometrical parameters of the M−like channel, namely height and width of elliptic obstacle, were considered. Based on the exhausted numerical results in the study, it has been found that the M−like channel exhibits more uniform and large molar concentration distribution of oxygen at the interface between catalyst layer and gas diffusion layer in the cathode side than the conventional parallel channel. Therefore, more reactants can participate in the electrochemical reaction in the catalyst layer, which improves the performance of proton exchange membrane fuel cell (PEMFC). Furthermore, effective evaluation criterion ( EEC ) was utilized to evaluate the comprehensive performance of PEMFC with the M−like channel. Comparing with the parallel channel, the M−like channel has better mass transfer performance without the penalty of high pressure drop, indicating better comprehensive performance. For the practical applications, optimum height and width of obstacle were obtained, the performance of which is 16% higher than the parallel channel.